Pengaruh Periklanan dan Harga Jual Terhadap Penjualan Produk Air Minum (Pada PT. Segara Bumi Persada) - Farih Ismawan (Universitas Mohammad Husni Thamrin, 2020)
This study aims to analyze whether advertising and selling prices have an effect on product sales. The hypothesis proposed in this study is that advertising and selling prices have a significant effect on product sales partially or simultaneously.The method used in this research is to do literature and field research. While the analysis model used is multiple regression analysis, multiple correlation coefficient analysis, multiple determination coefficient analysis, t-test statistical analysis and f-test hypothesis testing analysis and the method uses the SPSS-21 assistance program.Results Based on the research, it can be seen that the effect of Advertising and Selling Prices on Product Sales, either partially or simultaneously has a positive and significant effect. Keywords: Advertising, Selling Price, Product Sales